Flip of the jet head position of 3C 84 in 2015. Issue Volume 14:Issue S342(2018) (May 2018) - Kino, M.; Nagai, H.; Wajima, K.; Kawakatu, N.; Orienti, M.; Giovannini, G.; Hada, K.; Niinuma, K.; Giroletti, M.
Abstract: By performing the multi-epoch monitoring observation with KaVA at 43 GHz, we investigate the kinematics of the notable newborn bright component C3 located at the tip of the recurrent jet of 3C 84. During 2015 August-September, we discover the positional flip of the C3 component about 0.4 milli-arcsecond in angular scale. The flux density of the C3 component coherently showed the monotonic increase after the flip during our monitoring period. These phenomena are in good agreement with characteristic behaviors of a jet propagation in clumpy ambient medium predicted in hydrodynamical simulations.